2021
DOI: 10.5530/ijpcs.2021.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Physician’s Knowledge of Adverse Drug Reaction in Saudi Arabia

Abstract: Objectives: To state the physicians and dentists' knowledge and responsiveness of the adverse drug reaction (ADR) and reporting system in Saudi Arabia. Methods: It was a cross-sectional design of an authorized self-administered electronic survey about awareness and knowledge valuation of the ADR reporting system in Saudi Arabia. The electronic survey contained of demographic data and designated knowledge assessment of participants about the ADR reporting system. Results: The total number of participants was 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The KAP questionnaires that were utilized by the reviewed studies differ to great extent among the included 27 studies and did not follow a standardized validated measures nor standardized question items. Very few studies had indicated the performance of pilot test or applied internal consistency measures, which limit the development of representative conclusion assessing the knowledge, attitude and perception of HCPs toward ADR reporting [33,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The KAP questionnaires that were utilized by the reviewed studies differ to great extent among the included 27 studies and did not follow a standardized validated measures nor standardized question items. Very few studies had indicated the performance of pilot test or applied internal consistency measures, which limit the development of representative conclusion assessing the knowledge, attitude and perception of HCPs toward ADR reporting [33,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In general knowledge assessment of HCPs toward PV and ADR reporting indicated that pharmacists had better knowledge of PV, ADR reporting, and related policies and guidelines compared to physicians and nurses [16,21,27,33,39]. Knowledge comparison between hospital and community pharmacists revealed that hospital pharmacists are much more knowledgeable of the ADR reporting process, where and how to report ADR to the Saudi FDA PV system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations